2003
DOI: 10.1080/0953732032000051145
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Research Partnerships: A Managerial Perspective

Abstract: A Private sector incentives to participate in research partnerships can be grouped roughly into two categories: cost-economizing incentives and strategic incentives. This paper summarizes the argument in two streams of thought that are often identified with these two sides: the transaction-cost/incomplete contracts approach and the strategic management approach. The paper recounts business motives to engage in research partnerships in each and points out that differentiating between more traditional eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 47 publications
0
52
0
Order By: Relevance
“…For Hemphill & Vonortas (2003), the different theoretical approaches that have been proposed to understand the collaborative processes can be summarized in two schools of thought: costs-based partnerships and strategies-based partnerships. The first school is supported on Game theory to analyze the behaviour of the parties involved, and the influence of the transaction costs and the power dominance of a part in the success and maintenance of alliances (Kogut, 1988).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For Hemphill & Vonortas (2003), the different theoretical approaches that have been proposed to understand the collaborative processes can be summarized in two schools of thought: costs-based partnerships and strategies-based partnerships. The first school is supported on Game theory to analyze the behaviour of the parties involved, and the influence of the transaction costs and the power dominance of a part in the success and maintenance of alliances (Kogut, 1988).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Firms turning to partnerships as a means to address the challenges of innovation is a trend found in our survey and others (Cosner, 2010). Technology partnerships can have cost advantages (Hemphill & Vonortas, 2003) and strategic value (Mowery & Teece, 1996;Wessner, 2002) but add new challenges to managing projects (Stiglitz & Wallsten, 1999;Friend, 2006). These are all indications that management issues can be as important to the success of innovation as resources, technology, and markets.…”
Section: Project Management For Public-private Partnershipsmentioning
confidence: 92%
“…The main strategic guidance on partnerships from the DOE includes DOE-specific strategic plans DOE, 2011b) and CRADAs relies on a fairly passive announcement-application-review process. Private firms might seek out and court partners that meet their strategic interests (Hemphill & Vonortas, 2003;Hagedoorn, 1993), but the government is generally prohibited from such practices by competitive bidding rules. The relationship between partners is important for project success (Teece, 1992), but factors like cultural fit and complementary capabilities do not factor into the decision process until after the projects are selected.…”
Section: Current Process For Making Decisions About Energy Innovationmentioning
confidence: 99%
“…At the firm level, R&D has been recognized as important input factor to industrial production and studies have shown that the impact of R&D on productivity is substantial (Griliches, 1986;Griliches and Mairesse, 1984;Hall and Mairesse, 1995;. The successful creation of new knowledge and hence firm performance, however, has also been shown to often depend on the firms' engagement in collaborative R&D that combines resources, exploits complementary know-how, and internalizes R&D externalities (Teece, 1992;Shan et al, 1994;Das et al, 1998;Baum et al, 2000;Rothaermel, 2001;Dussauge et al, 2002;Hemphill and Vonortas, 2003;Rothaermel and Deeds, 2004;Powell and Grodal, 2005;Sampson, 2007).…”
Section: Introductionmentioning
confidence: 99%